Determination Of Selection Indices For Waterlogging-Stress Tolerance In Maize (Zea Mays L.) Under Field Conditions (Applied Biological Research, 2017)
Waterlogging is one of the serious constraints in maize production which  affects crop growth and yield in low lying areas. In order to study the  waterlogging tolerance in maize 60 line x tester crosses were evaluated during  kharif 2014 and 2015 under non-stress and waterlogging-stress conditions.  Thirteen selection indices including mean productivity (MP); geometric mean  productivity (GMP); harmonic mean (HM); tolerance index (TOL); stress susceptibility index (SSI); stress tolerance index (STI); yield index (YI); yield  stability index (YSI) and modified tolerance index under non-stress and stress  condition (KiSTI) were calculated using yield in non-stress (YP) and stress  condition (YS). The results showed that it was possible to identify superior  combinations for waterlogging tolerance based on above stress indices. Indices  STI, SSI, GMP, HM and YI were more accurate criteria for selection of  waterlogging-tolerant and high yielding hybrids. Positive and significant  correlation of MP, GMP, HM and STI with grain yield under both conditions revealed that these indices were more applicable and efficient for selection of  waterlogging tolerant genotypes. On the basis of STI, GMP, HM YI and KiSTI  WNCDMR11R1611 x LM-13, G24QC19-BBB-21-BBB × BML-6,  WNCDMR11R1611 × HKI-163 and S99TLYQ-HG-AB*4-47-BBB × BML-7  proved most waterlogging tolerant hybrids and produced good yield under  stress and non-stress conditions.
Keywords: Maize, stress tolerance; selection indices; waterlogging